Pengaruh Media Pembelajaran Berbentuk Majalah Digital Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Geografi - Kiyai, Risnawati Ramadhan; Lihawa, Fitryane; Rusiyah, Rusiyah (-, 2025)
Improving the quality of education requires significant advancements in various aspects, including curriculum development, learning innovation, and the provision of educational facilities and infrastructure. One approach that is believed to enhance the quality of learning is the use of digital-based media. The use of engaging learning media, such as digital magazines, is thought to increase students' interest and understanding of the subject matter, including Geography, which is often considered less engaging. However, the impact of using digital magazine-based learning media on students' learning outcomes in Geography has not been extensively explored, creating a gap that needs to be addressed. Therefore, this study aims to examine the effect of using digital magazine-based learning media on students' learning outcomes in Geography, employing an experimental method. The subjects of this research were students from classes X IIS 1 and X IIS 2. The results show that the use of digital magazine media significantly affects students' learning outcomes. Based on the t-test data analysis, a significant difference was found between the learning outcomes of students in the experimental class and the control class, with the average improvement in the experimental class being 83.94, while the control class showed an improvement of only 76.97. The t-test revealed a t-value of 4.013, which is greater than the t-table value of 1.859 at the α = 5% significance level, thus the hypothesis is accepted. These findings suggest that using digital magazines can be an effective alternative to improve students' learning outcomes in Geography. This research opens up the possibility for the broader application of digital learning media across various subjects, contributing to the development of innovative teaching methods that are in line with current technological advancements